Immunotherapy of osteosarcoma based on immune microenvironment modulation - Lian, Heping; Zhang, Jiakui; Hou, Shuna; Ma, Shuang; Yu, Jiachen; Zhao, Wei; Zhao, Duoyi; Zhang, Zhiyu (Frontiers in Immunology, 2025)
Osteosarcoma is a highly malignant tumor with unsatisfactory therapeutic outcomes achieved by chemotherapy, radiotherapy, and surgery. As an emerging oncological treatment, immunotherapy has shown potential in the clinical management of many tumors but has a poor response rate in osteosarcoma. The immunosuppressive microenvironment in osteosarcoma is the main reason for the ineffectiveness of immunotherapy, in which the low immune response rate of immune effector cells and the high activation of immunosuppressive cells contribute to this outcome. Therefore, modulating the function of the immune microenvironment in osteosarcoma is expected to remodel the immunosuppressive microenvironment of osteosarcoma and enhance the efficacy of immunotherapy. This article reviews the role of immune cells in the progression of osteosarcoma, describes the corresponding regulatory tools for the characteristics of different cells to enhance the efficacy of osteosarcoma immunotherapy, and concludes the prospects and future challenges of osteosarcoma immunotherapy.